Gynecologic Cancer InterGroup (GCIG) Consensus Review for Uterine and Ovarian Carcinosarcoma. (1st November 2014) - Berton-Rigaud, Dominique; Devouassoux-Shisheboran, Mojgan; Ledermann, Jonathan A.; Leitao, Mario M.; Powell, Matthew A.; Poveda, Andres; Beale, Philip; Glasspool, Rosalind M.; Creutzberg, Carien L.; Harter, Philipp; Kim, Jae-Weon; Reed, Nicholas Simon; et al.
Abstract : Abstract: Carcinosarcomas (also known as malignant mixed müllerian tumors) are rare and highly aggressive epithelial malignancies that contain both malignant sarcomatous and carcinomatous elements. Uterine carcinosarcomas (UCs) are uncommon with approximately more than 35% presenting with extra uterine disease at diagnosis. Up to 90% ovarian carcinosarcomas (OCs) will have disease that has spread beyond the ovary. Prognosis for localized stage disease is poor with a high risk of recurrences, both local and distant, occurring within 1 year. The survival of women with advanced UC or OC is worse than survival of endometrioid or high-grade serous histologies. No improvement in survival rates has been observed in the past few decades with an overall median survival of less than 2 years. Currently, there is no clear evidence to establish consensus guidelines for therapeutic management of carcinosarcomas. Until recently, gynecological carcinosarcomas were considered as a subtype of sarcoma and treated as such. However, carcinosarcomas are now known to be metaplastic carcinomas and so should be treated as endometrial or ovarian high-risk carcinomas, despite the lack of specific data. For UCs, a comprehensive approach to management is recommended with complete surgical staging followed by systemic chemotherapy in patients with both early and advanced stage disease. Active agents include paraplatin, cisplatin, ifosfamide, and paclitaxel. The combination of carboplatin-paclitaxel is the most commonly used regimen in the adjuvant and advanced setting. Adjuvant radiotherapy (external beam irradiation and/or vaginal brachytherapy) has not shown any overall survival benefit but has been reported to decrease local recurrences. For OCs and for other ovarian epithelial cancer, the mainstay of treatment remains cytoreductive surgical effort followed, even in early stage, by platinum-based chemotherapy, usually carboplatin-paclitaxel.